Mental god love when Spinoza - SHahda, Mohammad; Abd Alabrahim, Abd Alrahman (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The perception sbanusi in our salvation stems from a mental god of love, the result of this love necessarily about the nature of the soul that for as it was the first obsession is the Spiritual elation exemplified the god of the mental perspective in terms of essence the presence of human nature, which aims to know god through the partial things comte has a futuristic fantasy meaningful protect him making mistakes. And it portrays him in the form of god, conceived as eternal in opinion sbanusi is what he calls the mental love of god. So what we want to eat in our research this is the mental love emanating from the human knowledge of god when Spinoza which includes the and there is talk about the philosopher Spinoza and what are the effects and followed by the subject of research, which in turn is divided into two the first main axis: we turn the idea of god whet Spinoza, which make introduction to his book of morality and a sense of self in love mental issued by god. And how it manifested divine essence. The second axis: will we take it and the relationship between the human mind and the mind of god in sbanusi perspective.